Decision model about condom use: a multinomial logistic regression. - Isis Milane Batista de Lima; Ana Eloisa Cruz de Oliveira; Josemberg Moura de Andrade; Hemílio Fernandes Campos Coêlho; Kaline Silva Lima (Universidade de Brasília, 2016)
This work aims to present a study strategy to assist the decision making process about self-efficacy on condom use by multinomial logistic regression. The data analyzed refers to a sample composed of 1260 Brazilians, of which 36% reported always using condoms. According to the decision model considered, the variables indicated that the decision on condom use is modulated by the confidence that the individual feels about the success of its use. Keywords: Self-efficacy, condoms, logistic model.